Goethe yearbook, Volume XIV publications of the Goethe Society of North America - Richter, Simon (Boydell & Brewer, 2007)
The 'Goethe Yearbook,' first published in 1982, is a publication of the Goethe Society of North America and is dedicated to North American Goethe Scholarship. It aims above all to encourage and publish original English-language contributions to the understanding of Goethe and other authors of the 'Goethezeit,' while also welcoming contributions from scholars around the world. Volume 14 features a special section on childhood in the Age of Goethe, co-edited with Anthony Krupp. In addition, readers will find two essays illuminating Goethe's 'Triumph der Empfindsamkeit,' an inspired reading of 'Das Märchen' against the background of Goethe's critique of Newtonian science, a careful analysis of the daemonic in the poem 'Mächtiges überraschen,' and essays on Egmont and 'Wilhelm Meisters Wanderjahre. CONTRIBUTORS: KELLY BARRY, PAUL FLEMING, EDGAR LANDGRAF, LILIANE WEISSBERG, JOHN HEINS, HEATHER L. SULLIVAN, RALEIGH WHITINGER, ANGUS NICHOLLS, ROBIN A. CLOUSER. Simon J. Richter is professor of German at the University of Pennsylvania, and book review editor Martha B. Helfer is professor of German at Rutgers University. Anthony Krupp is assistant professor of German at the University of Miami
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Goethe, Johann Wolfgang von / 1749-1832 / Criticism and interpretation / Periodicals